Factors Influencing Consumers' Purchase Intention Towards Online Group Buying Websites - Era Fazirah, Kamaruddin (Universiti Malaysia Sarawak (UNIMAS), 2019)
Group-buying is a business. model based on the power of collective buying. Consumers with similar product interest come together and obtain a significant volume discount from retailers. Online group buying (0GB) is growing rapidly and it has become popular and successful in many countries. However, this area still lacks of research and it is still in the early stages of development especially in developing and emerging market. This study aims to examme the factors influencing consumers' purchase intention towards online group buying in the context of Kota Samarahan. Six dimensions were employed in measuring consumers' purchase intention in online group buying, such as perceived· usefulness (PU), perceived ease of us (PEOU), price, electronic word of mouth (e-WOM), trust and perceived risk (PR). A total of 384 valid samples were drawn from consumers who reside in Kota Samarahan.